Analisis Desain Komunikasi Visual Dakwah Pada Akun Instagram @nuonlinejatim Sebagai Media Dakwah di Era digital - Luthfi Hidayah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah bekerjasama dengan LP2M Institut Pesantren Sunan Drajat Lamongan, 2023)
In this digital era, da'wah is no longer limited to lectures on the pulpit, but because of the development of communication media, the way of delivering da'wah has expanded to more modern ways, one of which is through visual communication design. Today visual communication design is widely used to convey moral and religious messages, both through print and digital media. One of the social media that is widely used today as a medium for spreading da'wah messages through visual communication design is Instagram social media. Currently, one of the organizations that is intensively using Instagram as a propaganda medium is nuonlinejatim. In the modern era, visual communication design has begun to be widely applied to beautify the appearance so that it makes it easier for readers to understand the contents of the information. The scope of visual communication design is very broad, from simple forms such as posters, banners, pictures on social media to complex ones such as videography, animation and digital films.